2017
DOI: 10.1177/2324709617734012
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma Renal Crisis in Mixed Connective Tissue Disease With Full Renal Recovery Within 3 Months: A Case Report With Expanding Treatment Modalities to Treat Each Clinical Sign as an Independent Entity

Abstract: Mixed connective tissue disease (MCTD) is a rheumatologic overlap syndrome that can present with symptoms of systemic lupus erythematous, scleroderma, and polymyositis. A severe but rare complication that can occur in MCTD is scleroderma renal crisis. With multiple poor prognostic indicators, the renal outcome is usually poor. The clinical and histological picture is one of a thrombotic microangiopathy. Clinical suspicion has to be high for additional thrombotic or autoimmune processes coexisting due to associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Renal involvement in MCTD is uncommon (10%–26% of patients) and is often asymptomatic [ 5 ]. In a study looking at the renal involvement in MCTD, it was found that the only early indicator of renal disease was an abnormal urinalysis with no overt clinical features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Renal involvement in MCTD is uncommon (10%–26% of patients) and is often asymptomatic [ 5 ]. In a study looking at the renal involvement in MCTD, it was found that the only early indicator of renal disease was an abnormal urinalysis with no overt clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…MCTD can potentially affect various organ systems resulting in pulmonary, renal, cardiovascular, gastrointestinal, and central nervous system manifestations [ 3 , 4 ]. Scleroderma renal crisis (SRC) is an extremely rare complication in MCTD [ 5 , 6 ]. It typically presents as an accelerated hypertension of sudden onset and acute renal injury, with or without microangiopathic hemolytic anemia or thrombocytopenia [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 A worse prognosis for SRC exists in patients with dcSSc, cardiac involvement, renal crisis with normotensive blood pressures, and skin scores ≥20. 15 …”
Section: Discussionmentioning
confidence: 99%